Comparison of HIV-1 specific T cell immunity in the female genital tract and blood of HIV-infected women : impact of in vitro T cell expansion on HIV-specific T cell specificity, maturational status and functional complexity - Bere, Alfred (Division of Virology, 2014)
Includes bibliographical references (leaves 161-184).